Medical Technics - Ihde, Don (Forerunners: Ideas First, 2019)
A personal account of the aging body and advanced technologies by a preeminent philosopher of technology Medical Technics is a rigorous examination of how medical progress has modified our worlds and contributed to a virtual revolution in longevity. Don Ihde offers a unique autobiographical tour of medical events experienced in a decade, beginning in his 70s. Ihde offers experiential and postphenomenological analyses of technologies such as sonography and microsurgery, and ultimately asks what it means to increasingly become a cyborg. Forerunners: Ideas First Short books of thought-in-process scholarship, where intense analysis, questioning, and speculation take the lead